Evolusi dan Dampak Transformasi Perkembangan UMKM Digital Melalui E-Commerce Go Digital Mitra - Fariesta, Daffa; Sutrisno, Sutrisno (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
This research provides a comprehensive overview of the development and trasnformation of MSMEs (Micro, Small, and Medium Enterprises) in Indonesia in the era of digitalization, focusing on the Go Digital program by Bukalapak. The digital era has redefined the traditional paradigm of MSMEs, enabling them to access broader markets and interact directly with consumers through e-commerce platforms such as Bukalapak. This shift not only enhances the visibility and sales of MSMEs but also supports digital inclusion and empowers the local economy. With the Go Digital program, Bukalapal offers a platform that facilitates MSMEs to sell products online, while also providing support in aspects of marketing, logistics, and transaction security. This research highlights the importance of collaboration between the government and digital platforms to support the growth of MSMEs and the positive impact generated from this synergy, including enhancing the competitiveness of MSMEs in the global market and improving digital literacy. This research utulizes a normative legal research method, which is based on the study of norms and prevailing regulations, and their relevance to the technological developments in society within MSMEs. This reasearch examines constraints such as low digital literacy and logistical issues that need to be addressed, while also emphasizing the importance of understanding and seriously addressing these challenges to ensure the successful transformation of MSMEs through digital platforms.